Hubungan Pengetahuan Ibu dengan Perilaku Swamedikasi Batuk pada Balita di Posyandu Matahari Kecamatan Cimanggis Kota Depok - Valentina Dili Ariwati; Siti Mardiastuti Rinawati; Qonitah Khalda (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Mothers have a big role in caring for children. One of the mother's roles is to help children with health problems by allowing them to self-medicate, also known as self-medication. Coughing is a mild illness in toddlers that can be treated with self-medication. This study aims to determine the association between the level of knowledge of mothers and cough self-medication behavior in toddlers at Posyandu Matahari, Cimanggis District, Depok City. The study method used is an analytic survey with a cross sectional. The number of samples in the study were 110 mothers. The sampling technique used is purposive sampling. The results showed that there was an association between mother's knowledge and cough self-medication behavior in toddlers (p value = 0.32). The conclusion in this study is that mothers who have good knowledge will influence good cough self-medication behavior in toddlers.